Analysis Of The Work Posture Of Office Employees To Evaluate The Level Of Work Risk Using The Rapid Office Strain Assessment (ROSA) Method - Najib, Muhammad Abdullah; Andesta, Deny (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
Office ergonomics is a branch of ergonomics that covers the entire work environment (workstations) and work tools (especially using computers and chairs) in offices. Computer users or office workers often experience health problems related to musculoskeletal disorders (MSDs). The Secretariat and P3T BUMD Gresik Regency use a computer/laptop as the main work tool. Secretarial employees use computers for 8 (eight) hours daily, while P3T employees use computers for about 5 hours daily. The method used in this study was the Rapid Office Strain Assessment (ROSA). Assessment of work posture using the ROSA method on six office employees at BUMD Gresik Regency is divided into three sections. Section 1 assesses the height of the seat, the outside of the backrest seat surface, and the chair’s armrest. Section 2 conducts an assessment of the use of monitors and telephones. Section 3 assesses the use of mice and keyboards. Based on the calculation results using the ROSA method, the results obtained at the risk level value for each employee, namely, four employees have a high-risk level value or are at a dangerous/risky level and need to be repaired immediately. The other two employees indicate a safe / non-risky risk level.